Conjugate Heat Transfer of Laminar Air Flow in Rectangular Mini Channel (Journal of Engineering, 2022)
Conjugate heat transfer has significant implications on heat transfer characteristics, particularly in thick wall applications and small diameter pipes. In this study, a three-dimensional numerical investigation was carried out using commercial CFD software “ANSYS FLUENT” to study the influence of conjugate heat transfer of laminar flow in mini channels at constant heat flux wall conditions. Two parameters were studied and analyzed: the wall thickness and thermal conductivity and their effect on heat transfer characteristics such as temperature profile and Nusselt number. Thermal conductivity of (0.25, 10, 202, and 387) W/m2C and wall thickness of (1, 5, and 50) mm were used for a channel of (1*2) mm cross-sectional dimensions. Taking the Reynolds number 800 for all cases. The results demonstrate that the conjugate conduction impact is observed at high conductivities and for large wall thicknesses in the studied materials. This impact flattened the wall temperature distribution along the channel wall instead of being an augmented linear profile. Also, it flattens the local Nusselt number due to the axial heat conduction along the walls. It reduces the effect of the entrance region of high Nusselt number while making the fluid temperature profile curved and redistributing the wall heat flux and accumulating it toward the leading edge. A decrease was observed in the average Nusselt number of 8% when increasing wall thickness from 1 mm to 50 mm for the same thermal conductivity of 10 W/m2C, while an increase in Nusselt number of 19% with thermal conductivity changes from 0.25 W/m2C to 10 W/m2C.